Ionic Liquid, [bmim]Br, as An Efficient Promoting Medium for Synthesis of 2-Amino-3,5-dicarbonitrile-6-thiopyridines - Davoodnia, A.; Attar, P.; Eshghi, H.; Morsali, A.; Tavakoli-Hoseini, N.; Tavakoli-Nishaburi, A. (Asian Journal of Chemistry, 2010)
A simple, efficient and rapid method for the synthesis of 2-amino-3,5-dicarbonitrile-6- thiopyridines through one-pot multi-component reaction of a variety of aryl aldehydes with malononitrile and thiophenol in the presence of ionic liquid 1-butyl-3-methylimidazolium bromide, [bmim]Br, as an efficient promoting medium without the use of any catalyst has been developed. This method has the advantages of good yields, milder reaction conditions, no catalyst and environmentally benign procedure.